Recent advances in bacteria-mediated cancer therapy - Liang, Shuya; Wang, Chao; Shao, Yingchun; Wang, Yanhong; Xing, Dongming; Geng, Zhongmin (Frontiers in Bioengineering and Biotechnology, 2022)
Cancer is among the leading cause of deaths worldwide. Although conventional therapies have been applied in the fight against the cancer, the poor oxygen, low extracellular pH, and high interstitial fluid pressure of the tumor microenvironment mean that these treatments fail to completely eradicate cancer cells. Recently, bacteria have increasingly been considered to be a promising platform for cancer therapy thanks to their many unique properties, such as specific tumor-targeting ability, high motility, immunogenicity, and their use as gene or drug carriers. Several types of bacteria have already been used for solid and metastatic tumor therapies, with promising results. With the development of synthetic biology, engineered bacteria have been endowed with the controllable expression of therapeutic proteins. Meanwhile, nanomaterials have been widely used to modify bacteria for targeted drug delivery, photothermal therapy, magnetothermal therapy, and photodynamic therapy, while promoting the antitumor efficiency of synergistic cancer therapies. This review will provide a brief introduction to the foundation of bacterial biotherapy. We begin by summarizing the recent advances in the use of many different types of bacteria in multiple targeted tumor therapies. We will then discuss the future prospects of bacteria-mediated cancer therapies.